2005
DOI: 10.17221/3777-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth regulators on plant regeneration in tomato

Abstract: ABSTRACT:We studied the effect of different plant growth regulators on in vitro regeneration and plant growth of three cultivars of tomato (Lycopersicon esculentum Mill.) from explants derived from hypocotyls and cotyledons of aseptically grown seedlings. The regeneration capacity was significantly influenced by cultivar and explant type. The highest number of shoots regenerated in both types of explants was recorded on MS medium supplemented with 1.0 mg/dm 3 zeatin and 0.1 mg/dm 3 IAA. The cultivar UC 82 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Results of this experiment confirmed the positive influence of growth regulator on the number of shoots regenerated from tomato cotyledons, leaf and hypocotyls. Our experiments supported the results of other authors (Nogueira et al, 2001;Gubis et al, 2004) where most efficient medium for in vitro regeneration of tomato was induction medium supplemented with a cytokinin. Devi et al (2008), studying the morphogenesis in 4 cultivars of tomato viz.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results of this experiment confirmed the positive influence of growth regulator on the number of shoots regenerated from tomato cotyledons, leaf and hypocotyls. Our experiments supported the results of other authors (Nogueira et al, 2001;Gubis et al, 2004) where most efficient medium for in vitro regeneration of tomato was induction medium supplemented with a cytokinin. Devi et al (2008), studying the morphogenesis in 4 cultivars of tomato viz.…”
Section: Discussionsupporting
confidence: 92%
“…Various combinations of auxins/cytokinins have been used to study their effect on regeneration (Rao et al, 2005). Gubis et al (2004), observed that zeatin (1 mg/L) and IAA (0.1 mg/L) supplemented media had 100% regeneration frequency with hypocotyl explants in all genotypes studied. However, we obtained a regeneration frequency of 74%, 71% and 64% for hypocotyls explants in medium C, B and A, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The in vitro morphogenetic responses of cultured plants are affected by different components of the culture media and therefore, it is important to evaluate their effects on plant callus induction and regeneration (Gubis et al, 2004). The surface sterilized germinating seeds were used as sources of explants for callus induction.…”
Section: Callus Induction On Hypocotyl and Cotyledon Explantsmentioning
confidence: 99%
“…Various authors (Munshi et al, 2007;Gubis et al, 2004) reported that hypocotyl explants were superior to cotyledon in shoot regeneration efficiency and shoot length. MS medium supplemented with 2 mg/L BAP was the most effective in adventitious shoot formation and shoot length in both explants and cultivars.…”
Section: Effects Of Bap On Callus Inductionmentioning
confidence: 99%